Local Knowledge and Practice of Entomophagy in Datengan Village, Kediri, East Java, Indonesia - Whisnu Febry Afrianto; Laeli Nur Hasanah; Rivandi Prananditaputra; Taufiq Hidayatullah; Susanti Indriya Wati; Yasri Syarifatul Aini; Budiyoko Budiyoko (Sriwijaya Journal of Environment, 2022)
Malnutrition is one of the serious problems encountered by Indonesia. This research aimed to identify local knowledge and practice on entomophagy in Datengan Village, Kediri, East Java, Indonesia. The entomophagy data were collected by the qualitative approach. The edible insects in this study were honey bee (i.e., Apis mellifera, A. cerana, and A. dorsata) and flying termites (i.e., Macrotermes gilvus and Odontotermes javanicus). All aspects of the local and scientific name, halal status, harvest period, local value, and how to collect, prepare, cook and serve have been described in this article. According to the Indonesian Council of Religious Scholars, termites are halal or allowed to be consumed (it could otherwise be haram, if people feel disgusted). On the other hand, consuming bees (A. mellifera, A. cerana, and A. dorsata) is haram to eat adult bees. Meanwhile, consuming bees that are still in the form of larvae is halal, but it is to be haram if they are eaten separately with honey or hive. There were five challenges in entomophagy such as disgust, allergy, inferior, halal status, and complicated processing methods.